Dampak Terapi Floortime terhadap Perkembangan Keterampilan Sosial Anak Autisme di UPTD SMP Negeri 18 Depok (International Forum of Researchers and Lecturers, 2026)
The increasing number of children with autism spectrum disorder in Indonesia presents new challenges for the inclusive education system, particularly in the development of social skills. This study aims to analyze the impact of floortime therapy on the development of social skills in children with autism at UPTD SMP Negeri 18 Depok City. The study employed a qualitative approach using a case study method, with data collected through observation, interviews, and documentation. The theoretical framework was based on the floortime implementation theory proposed by Greenspan and Wieder (2006) and the social skills theory by Rachmah (2018). The results indicate that floortime therapy has a positive impact on improving the social skills of children with autism, particularly in aspects of attention and engagement, two-way communication, sharing ideas and emotions, and logical thinking. The effectiveness of the therapy is further enhanced by the contribution of the surrounding environment, including family members, teachers, peers, and therapists, who play an important role in supporting the sustainability of the intervention. These findings emphasize that floortime therapy is not only effective as a therapeutic approach but also serves as a supportive strategy in improving the quality of inclusive education services for children with special needs.